ANALISIS PENDAPATAN NELAYAN JARING INSANG (GILL NET) DI DESA PANIPAHAN TELUK PULAI KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR - Tibrani (UIR Press, 2021)
This study aims to identify and analyze the characteristics and business profile of gill net fishermen, gill net fishing technology, and catching costs and income of gillnet fishermen in Panipahan Teluk Pulai Village, Pasir Limau Kapas District, Rokan Hilir Regency. This study used a survey method for gill net fishermen. Data collection was carried out by census from 15 fishermen and consisted of primary data and secondary data. The data was analyzed by using descriptive qualitative and quantitative analyses. The results showed that the average age of fishermen was 34.8 years, the education level of fishermen was 7.4 years, the length of business experience was 12.26 years, and the number of family was 3 people. The business profile in the form of a business is an individual business and the business scale is a micro business. The fishing technology used a motorboat with an engine power of 6-7 Gt, the operation was carried out by the owner fisherman with 4 crew members. The gill nets were used with a mesh size of 3.5 inches and a net length of 1,320 m. The average cost of production/capture of gillnet fishermen was IDR 2,408,800 for variable costs, IDR 261,060 for fixed costs, and IDR 1,839,895 for crew members. The income of fishermen who own gill nets was IDR 7,269,598/trip and the profit of owner fishermen was IDR 2,759,843/trip. The value of the R/C ratio was 1.6, indicating that the fishing businesses were feasible because the RCR value was more than 1 and the production BEP of gillnet fishermen was 203,316 kg. It means that gill net fishermen must produce 203,316 kg for return on investment and BEP Price is IDR 13,760. It means that gill net fishermen have to sell their catch at a price of IDR 13,760 for returning of investment.